Clinical characteristics classified by the serum KL-6 level in patients with organizing pneumonia - Yamaguchi, K.; Tsushima, K.; Kurita, N.; Fujiwara, A; Soeda, S.; Yamaguchi, A.; Sugiyama, S.; Togashi, Y; Kono, Y.; Kasagi, S.; Setoguchi, Y (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Background: The serum Krebs von der Lungen-6 (KL-6) level is a useful marker correlated with the severity of various interstitial lung diseases. There have been few reports about the clinical characteristics of organizing pneumonia (OP) associated with the serum KL-6 levels. Objective: This study was performed to determine whether the serum KL-6 levels can help determine the optimal treatment for OP. Designs: Patients diagnosed with OP by clinical, radiological and histopathological findings were retrospectively reviewed. The OP patients were classified into two groups based on their serum KL-6 levels: normal KL-6 and high KL-6 groups.The two groups were compared with regard to their clinical and radiological data and therapeutic response one month after the start of treatment.Results:The clinical records of twenty-two patients diagnosed withOP were reviewed.The serumKL-6 level was elevated in 11 of the 22 patients.There were no obvious differences in the clinical data between the two groups, although patients in the normal KL-6 group tended to have a fever. There were no significant differences in the chest X-ray (CXR) score or computed tomography (CT) score between the two groups. The CXR scores were correlated with the serum KL-6 levels.At 1 month after the diagnosis, 11 patients who needed treatment with prednisolone were included in the high KL-6 group. Conclusions: Patients with normal KL-6 levels showed lower CXR and CT scores. The serum KL-6 level on admission is a useful marker to judge the need for corticosteroid treatment in OP patients.